An equal music - Seth, Vikram 1952- (Broadway Books, 1999)
A second-time-around romance between Michael, a violinist and Julia, a pianist. He runs into her on a London bus and learns she is married to a banker and has a son. They resume their love, but drama lies ahead as Julia is going deaf. By the author of A Suitable Boy.
Keywords: Chamber music groups -- Fiction; Pianists -- Fiction; Violinists -- Fiction; Geiger; Pianistin; Liebesbeziehung; London; Fiktionale Darstellung; Love stories